A review of maize-beans and maize-cowpea intercrop systems in the semiarid northeast Brazil - Rao, M. R.; Morgado, L. B. (Pesquisa Agropecuaria Brasileira, 2014)
Fifty-one experiments on maize -beans and 34 on maize-cowpea intercropping systems conducted mostly in the semiarid Northeast Brazil were analysed to get an understanding of the performance of these intercrops in terms of their productivity as well as stability. Both the intercrop systems produced higher yields over their respective sole crops under a wide range of agroclimates; the average advantage with maize-beans was 32%, while that from maize-cowpea was 41%. The optimum row proportion for maize-beans was one maize: three beans, requiring 50% of sole crop maize population and 75% sole bean population. In maize-cowpea, alternate rows or one maize: two cowpea arrangement with about 50% of sole maize density and 100% of sole cowpea population seemed to be optimum. The intercrop yields showed the same degree of variability as those of the sole crops, but the intercrops being more productive were somewhat less risky than the sole crops. The intercrops failed less frequently compared to sole crops to meet specified incomes or yields. Sorghum seemed to be a good alternative to the traditional cereal because of its improved and consistent performance. Future research needs are discussed tor further yield improvement in these two intercrop systems.